A Systematic Characterization of Artificial Intelligence Business Models as a Fundament for Business Model Innovation and Strategic Decision-Making - Wilga, Matthäus; Jalowski, Max; Kirschbaum, Julius; Roth, Angela (21st European Academy of Management (EURAM) Conference 2021, 2021)

Boost Or Bust: Characterizing Value Co-Creation With AI-Based Non-Human Agents From A User Perspective - Wilga, Matthäus; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (13th SERVSIG Conference, 2024)

Characterizing the Roles of AI-Enabled Non-Human Agents in Service Systems - Wilga, Matthäus; Hajjam, Layla; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (19th International Conference on Wirtschaftsinformatik, 2024)
Machines are becoming more versed at adapting to environmental impulses and their operational contexts, changing their roles in service systems. These machines can autonomously fulfill goals within defined boundaries set by legal actors and thereby exhibit agency. As interactions are at the core of services, the integration of such non-human agents into value co-creation has the potential to heavily impact the innovation of services. Following a four-step type construction approach based on empirical open-source data on 130 services, we develop a multi-dimensional characterization of six roles that non-human agents fulfill in service systems. Taking a systemic perspective, we identify service system interactions involving non-human agents and how their contributions impact value propositions. Our findings forward the understanding of service processes involving non-human agents and their impact on value co-creation, benefiting both theory and practice through knowledge on the engineering of service systems and value-driven, user-centered human-machine interaction

Dienstleistungswende zur Nachhaltigkeit - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Kurtz, Christian; Lewandowski, Tom; Wilga, Matthäus; Hottum, Peter; Schemmer, Max (2023)

Innovation KI-basierter Dienstleistungen für die industrielle Wertschöpfung – Ein artefaktzentrierter Ansatz - Jalowski, Max; Roth, Angela; Oks, Sascha Julian; Wilga, Matthäus (Künstliche Intelligenz im Dienstleistungsmanagement, 2021)
Dieser Beitrag zeigt auf, wie insbesondere für kleine und mittlere Unternehmen die Gestaltung und Innovation von KI-basierten Dienstleistungen in der industriellen Wertschöpfung unterstützt werden kann. Dazu werden Herausforderungen bei der Entwicklung KI-basierter Dienstleistungen erhoben und anschließend Artefakte präsentiert, die zur Innovation von Dienstleistungen zum Einsatz kommen. Diese werden basierend auf den zuvor identifizierten Herausforderungen adaptiert, um die Innovation von KI-basierten Dienstleistungen zu ermöglichen.<br

KI-Paradigmenwechsel der Wertschöpfung: Die Triade "Dienstleistung - Arbeit - KI" gestalten - Roth, Angela; Benz, Carina; Wilga, Matthäus; Satzger, Gerhard; Böhmann, Tilo; Hottum, Peter; Lewandowski, Tom (2023)

Partizipation und Un_gleichzeitigkeit - Bella, Natalie; Gamradt, Julia; Staples, Ronald; Widuckel, Werner; Wilga, Matthäus; Whittall, Michael (Springer VS, 2022)
Das Buch befasst sich mit der digitalen Transformation in Unternehmen und fragt nach den Veränderungen für die betrieblichen Stakeholder. Im Mittelpunkt steht der Umgang von betrieblicher Mitbestimmung mit digitaler Transformation. Dies setzt auch eine Transformation betrieblicher Mitbestimmung selbst auf die Tagesordnung, die die direkte Partizipation der Beschäftigten an der interessenpolitischen Positionierung des Betriebsrats und deren Durchsetzung gegenüber dem Arbeitgeber deutlich erweitert und zu einer strategischen Ressource der Mitbestimmung werden lässt.<br
Keywords: Mitbestimmung; Betriebsrat; Digitalisierung; digitale Transformation; Ungleichzeitigkeit; qualitative Sozialforschung; Arbeit; industrielle Beziehungen; Organisationsfallstudie; Fallstudie; Partizipation; Innovative Organisationsformen; Digitalisierung der Arbeitsabläufe; Chancengleichheit

Value Creation in the Information Economy: The Triad of AI, Service, and Human Work - Roth, Angela; Benz, Carina; Wilga, Matthäus; Hottum, Peter; Langes, Barbara; Lewandowski, Tom; Nägele, Rainer; Peters, Christoph; Satzger, Gerhard (Journal of Service Management Research, 2024)
Advancements in artificial intelligence (AI), particularly generative AI (GenAI), have revolutionized the value generation in service<a href="https://unihamburgde-my.sharepoint.com/personal/christian_kurtz_uni-hamburg_de/Documents/DL2030/Phase 4/Ziel 3 - Weiterentwicklung der Schwerpunktthemen/02_Triade_Dienstleistung_KI_Arbeit/SMR Journal Article/Final Submission/Roth et al_Revised Version_Value Creation in the Information Economy.docx#_ftn1" title="">[1] as well as work processes and the work environment. However, the transformative potential of AI in the context of service and work must be guided in a way that ensures its alignment with human-centric values and economic goals. Based on an interactive panel and three workshops of service researchers and practitioners at the annual conference of the German Forum for Service Research (DF)² in September 2023, this paper highlights six fields of action. Spanning corporate strategy, processes, and technology, these six fields of action illustrate how future-oriented service research may harness the opportunities of AI for society and the economy, manage associated risks, and foster societal acceptance. They serve as a framework for discussions and initiatives in service research, raise awareness among companies about necessary changes to remain competitive, and highlight funding needs with high relevance, societal importance, and economic potentia
Keywords: Service Research Priorities; Generative AI; Future of Work; Value Creation